1981
DOI: 10.1136/gut.22.7.566
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on cellular and humoral chemotaxis in Crohn's disease using the under agarose gel technique.

Abstract: SUMMARY The locomotor function of polymorphonuclear cells (cellular chemotaxis) and serum chemotactic activity (humoral chemotaxis) were studied in 51 patients with Crohn's disease using a method of migration under agarose gel. To study cellular chemotaxis patient's polymorphonuclear cells were challenged against normal Zymosan activated serum and humoral chemotaxis was evaluated testing the patient's Zymosan activated serum against normal polymorphonuclear cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Steroids, sulphasalazine, and its active metabolite 5 amino salicylic acid are all potent inhibitors of leucocyte motility.20 During treatment with steroids a decreased chemo-attractant activity of complement activated serum has recently been shown in Crohn's disease. 21 We were able to extend these results by detecting a similar dysfunction of complement in a group of patients which had not received any drugs for at least three months.…”
Section: Discussionmentioning
confidence: 55%
“…Steroids, sulphasalazine, and its active metabolite 5 amino salicylic acid are all potent inhibitors of leucocyte motility.20 During treatment with steroids a decreased chemo-attractant activity of complement activated serum has recently been shown in Crohn's disease. 21 We were able to extend these results by detecting a similar dysfunction of complement in a group of patients which had not received any drugs for at least three months.…”
Section: Discussionmentioning
confidence: 55%
“…Since this work was carried out, O'Morain et al have also reported normal neutrophil motility in Crohn's disease using a Boyden chamber filter assay,15 as have D'Amelio and colleagues using an agarose plate assay 16. These findings make untenable the hypothesis that Crohn's disease results from Casein-stimulated chemotaxis (microns moved by leading cellfront in 120 minutes) ofmonocytes from normal subjects andfrom patients with Crohn's disease or ulcerative colitis (mean ± SD).…”
mentioning
confidence: 76%
“…Two other studies have also shown that prednisolone therapy fails to affect neutrophil chemotaxis. 16 21 All these studies have, however, been performed with leucocytes that have been washed and then incubated in the absence of the patient's serum. Both prednisolone22 23 and sulphasalazine23 inhibit chemotaxis when added to leucocytes in vitro so a therapeutic effect on chemotaxis in vivo cannot be completely excluded, particularly if these drugs are present in the colon in high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Three groups have stud ied chemotaxis towards both casein and complement-derived chemoattractants; two groups [1,3] found the results in Crohn's dis ease did not differ from controls but one group [6] found a difference by a factor of two, being lower with C5a. Several reports showed no relationship between chemotaxis and disease activity [1,3,4,6,8,9] but in two studies chemotaxis improved as patients improved clinically [10,11]. Depressed che motaxis in Crohn's disease may [8,9,12] or may not [3,7,11] be due to serum inhibi tors.…”
mentioning
confidence: 99%
“…In vitro chemotaxis towards ca sein may be normal [1][2][3][4][5][6] or depressed [7,8], Chemotaxis towards complement-derived chemoattractants may also be normal [1,3,9] or depressed [6]. Three groups have stud ied chemotaxis towards both casein and complement-derived chemoattractants; two groups [1,3] found the results in Crohn's dis ease did not differ from controls but one group [6] found a difference by a factor of two, being lower with C5a.…”
mentioning
confidence: 99%